Pemahaman moderasi beragama pada siswa Madrasah Aliyah Negeri Kota Samarinda - Syahid, Abdul; Fauzan, Umar; Malihah, Noor (Tawazun: Jurnal Pendidikan Islam, 2023)
This study aims to determine students' understanding of religious moderation in Islamic educational institutions, especially Madrasah Aliyah Negeri 2 Samarinda City. There are concerns that educational institutions labeled as religion are easy to be infiltrated by the notions of radicalism, intolerance & liberalism, so researchers conducted research on students' understanding of religious moderation. This study uses qualitative methods with a descriptive analysis approach, data collection techniques through observation, interviews & documentation. The results of the study, after observing the attitudes, behavior & activities of students in the field & the results of interviews with teachers, show that students' understanding of religious moderation is very good. This understanding can be seen from several indicators of national commitment, tolerance, anti-radicalism & accommodating local culture. Abstrak Penelitian ini bertujuan untuk mengetahui pemahaman siswa terhadap moderasi beragama di lembaga pendidikan Islam khususnya Madrasah Aliyah Negeri 2 Kota Samarinda. Adanya kekhawatiran terhadap lembaga pendidikan yang berlabel agama mudah untuk tersusupi paham radikalisme, intoleransi dan liberalisme, maka peneliti melakukan penelitian tentang pemahaman siswa terhadap moderasi beragama. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis deskriptif, teknik pengambilan data melalui observasi, wawancara dan dokumentasi. Hasil penelitian, setalah melalui observasi pada sikap, perilaku dan kegiatan siswa di lapangan dan hasil wawancara pada guru menunjukkan bahwa pemahaman siswa terhadap moderasi beragama sangat baik. Pemahaman tersebut terlihat dari beberapa indikator komitmen kebangsaan, toleransi, anti radikalisme dan akomodatif budaya lokal.